The image as the body’s other: considerations on image Anthropology in Hans Belting and Dietmar Kamper - Heilmair, Alex Florian; Baitello Junior, Norval (MATRIZes, 2019)
The purpose of this article is to present an alternative approach to the image sciences, as yet little explored, which work from the perspective of the body. We will start from the bioanthropological premise that the body claims for body, and will seek to think about the image based on Hans Belting’s image anthropology, mainly in relation to the theoretical triangulation of image, media and body, alongside Dietmar Kamper’s sociology of the body, whose critical diagnosis of current media culture and of its excessive self-referentiality demonstrates an unwanted immanence of the imaginary. We will also include those authors who have contributed to the Kamperian diagnosis: Vilém Flusser, Günther Anders, Jean Baudrillard, Byung-Chul Han and Christoph Wulf.